2012
DOI: 10.2214/ajr.11.8014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pulmonary CT of Children

Abstract: Wide-detector dynamic CT is ideal for evaluation of the airway and lungs in infants and small children with persistent respiratory distress. Effective doses are low, typically less than 2 mSv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 13 publications
(23 reference statements)
2
63
0
1
Order By: Relevance
“…As previously suggested by Greenberg S.B. et al, our study confirmed that congenital heart disease is often associated with airway abnormalities and in particular left bronchomalacia was described for almost all children previously surgically treated …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As previously suggested by Greenberg S.B. et al, our study confirmed that congenital heart disease is often associated with airway abnormalities and in particular left bronchomalacia was described for almost all children previously surgically treated …”
Section: Discussionsupporting
confidence: 90%
“…et al, our study confirmed that congenital heart disease is often associated with airway abnormalities and in particular left bronchomalacia was described for almost all children previously surgically treated. 4 In the majority of cases (89%) the agreement between DB and the dynamic CT scan was great and both agreed when negative or described the same airway malformation. This encouraging result confirms in children what previously described in 29 adults by Lee K.S.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Aided by sedation or anesthesia, we are now able to routinely acquire motionless images of the tracheobronchial tree at full inspiration and end-expiration [42] in a cross-sectional format [17][18][19]43]; however these acquisitions do not truly investigate the dynamic nature of tracheo-bronchomalacia. To address this, others have developed free-breathing cine chest CT [44,45] and "four-dimensional" CT on a scanner with enough detectors to cover the relevant anatomy without need for table motion [9,[46][47][48][49]. Yet, I have found that my results with these techniques usually did not affect the clinical management of dynamic airway collapse because most children eventually outgrow this condition and bronchoscopy has remained the diagnostic gold standard for this condition at my hospital [50].…”
mentioning
confidence: 99%